2010
DOI: 10.1007/s10750-010-0117-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antifungal substances on some zoosporic fungi (Kingdom Fungi)

Abstract: Zoosporic fungi constitute a large group of true fungi which inhabit freshwater, brackish, marine and soil ecosystems. In general, very little is known about the effects of antifungal substances on the growth and survival of most species. This review focuses on experimental research with those isolates which have been studied, especially in some species of Synchytrium, Olpidium, Batrachochytrium, Allomyces, Blastocladiella, Neocallimastix. These genera represent genetically diverse groups. Although the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods. Generally, ascomycetes can be frequently and easily isolated in deep-sea environments, but chytrids and other basal fungi may be missed because many chytrids can not be isolated on solid growth media, especially those to which chloramphenicol has been added (Gleason and Marano 2011). …”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods. Generally, ascomycetes can be frequently and easily isolated in deep-sea environments, but chytrids and other basal fungi may be missed because many chytrids can not be isolated on solid growth media, especially those to which chloramphenicol has been added (Gleason and Marano 2011). …”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…For instance in fish farm sediments, the number of bacteria declined by 50–67% due to the application of antibiotics [ 8 ], whereas in agricultural soils application of sulfonamide antibiotics could affect bacterial community structure [ 9 ]. Similarly, fungi are often sensitive to antifungal substances that dramatically constrain their community structure to the few resistant strains [ 10 ]. However, fungi are generally more resistant to biocides than bacteria [ 11 ], which is mostly due to their composition of outer cell layers with chitin.…”
Section: Introductionmentioning
confidence: 99%
“…However, Chytridiomycota have also been detected as one of the major fungal components in several deep-sea environments, such as hydrothermal vents and methane cold seeps, but only by culture-independent methods (Nagano and Nagahama, 2012). In contrast, very few species have been detected in surface marine waters using both culture-and cultureindependent approaches (Massana and Pedrós-Alió, 2008;Gleason and Marano, 2011;Richards et al, 2012;Lepelletier et al, 2014). Therefore, culture-independent molecular probing of potentially infected organisms could reveal important new information about interactions with marine fungi.…”
Section: Introductionmentioning
confidence: 99%